Lower Limb Reconstruction with Tibia Allograft after Resection of Giant Aneurysmal Bone Cyst - Joaquim Soares do Brito; Joana Teixeira; José Portela (Case Reports in Orthopedics)
Aneurysmal bone cysts (ABCs) are benign, expansible, nonneoplastic lesions of the bone, characterized by channels of blood and spaces separated by fibrous septa, which occur in young patients and, occasionally, with aggressive behavior. Giant ABC is an uncommon pathological lesion and can be challenging because of the destructive effect of the cyst on the bones and the pressure on the nearby structures, especially on weight-bearing bones. In this scenario, en bloc resection is the mainstay treatment and often demands complex reconstructions. This paper reports a difficult case of an unusual giant aneurysmal bone cyst, which required extensive resection and a knee fusion like reconstruction with tibia allograft.